Growth performance of Boran and their Simmental crossbred calves at Adami Tulu - Sisay, A.; Ebro, A. (Ethiopian Society of Animal Production, 1988)
Calf records on 118 Boran and their Simmental crosses of different blood levels were analyzed to investigate the effect of Simmental blood level on birth, weaning, yearling and maturity weight, and pre- and post-weaning growth rate of calves. There was no significant difference in birth and weaning weights between crossbred and purebred calves. But calves with 37.5% Simmental blood were significantly heavier at yearling than those with 25%, and they were heavier at maturity than other groups of animals. During pre-weaning, 37.5% Simmental calves grew significantly faster than 62.5% Simmental calves and in the post-weaning they continued to grow faster. The pre- and post-weaning growth rates of 62.5% Simmental calves were inferior to that of Boran, suggesting possible problems of adaptation for calves with higher exotic blood levels. Male calves were 12.6 kg heavier than females at weaning. Male calves grew faster than females both in pre-weaning (22.5g/d faster) and post-weaning (20.8g/d). Calves born during wet season were heavier at birth and at weaning, and they grew faster during pre- and post-weaning periods than calves born in dry season. The highest mortality rate was observed in pre-weaning growth period in all groups of calves. Pre-weaning mortality rate was higher in Boran calves followed by calves with 25% Simmental.